Improving psychological security and empowerment: New model for nurses toward the care of potential organ donors - Hamideh Yazdimoghaddam; Zahra Sadat Manzari; Abbas Heydari; Eesa Mohammadi (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Caring for brain dead patients is the heaviest of duties for nurses, and despite tremendous stress, there are no theories/models to support nurses in this situation. This study designed a supportive model for nurses to provide care for potential organ donors. MATERIALS AND METHODS: This qualitative study was conducted in two stages. In the first stage, semi-structured interviews with 31 nurses and other stakeholders, observation and field notes continued until data saturation, (on 2018), were analyzed using continuous and comparative analysis through Corbin-Strauss method. In the second stage, theory synthesis of Walker and Avant's strategies for theory construction (2011) was used to design a supportive model/theory. The theory synthesis includes three stages: (i) selection of focal concept (the concept of "moral obligation to provide holistic care until the last minute" was selected); (ii) review of studies to identify the factors related to focal concept relevant studies (42 articles were reviewed, statements and concepts related to focal concept were then extracted and classified, and their relations were specified); and (iii) organization of concepts and statements within a relevant general and effective manifestation of the phenomenon under study which led to developing of a model. RESULTS: In this supportive model/theory, "improving psychological security and empowerment" was conceptualized within the conceptual framework. This supportive model entails three main components, including (i) informational and educational support, (ii) systematically support, and (iii) management support. CONCLUSIONS: According to the results, nurses with moral obligation to provide holistic care were faced with several challenges. Therefore, it is recommended that the healthcare system take supportive proceedings for nurses in various fields of the care for brain dead patients to resolve educational, moral, and legal challenges. This supportive model is essential for maintaining the nurses' health, increasing the quality of nursing care and the health of potential transplant organs.